STUDENTS' ENGAGEMENT IN ENGLISH LEARNING - Azhar, Lathifah Ghoida (2013)
This paper entitled Students' engagement in English Learning is a report of qualitative study which explores characteristics of students' engagement in English learning at one of junior high schools in Bandung. It used descriptive method to present the findings and data discussions. The data were gained using questionnaire, observation, and interview aiming to provide description on students' engagement in English class and students' perception on their own engagement. The result shows that students' engagement in English learning does not yet reach the full level of engagement, but it has reached more than half of it. Students' engagement has been believed as an essential factor in leaning, so hopefully the result of this research can help teachers in improving students' engagement in English learning and enhancing their teaching skill.For further research, it is suggested to add other characteristics and try to conduct the research in different level of education in order to provide broader description on students' engagement in English learning.